Mesoporous and adsorptive properties of palm date seed activated carbon prepared via sequential hydrothermal carbonization and sodium hydroxide activation - Md. Azharul, Islam; I.A.W., Tan; A., Benhouria; M., Asif; B.H., Hameed (Elsevier B.V., 2015)
Mesoporous activated carbon (AC) was prepared via sodium hydroxide (NaOH) activation of hydrochar from the hydrothermal carbonization (HTC) of palm date seed (PDS). The textural, morphological, and chemical properties of the produced hydrochar AC were investigated. NaOH activation enhanced the porosity and surface functionality of the hydrochar. Batch equilibration methods were performed to explore the process parameters that affected the adsorption of the prepared AC on methylene blue (MB), including initial concentration, contact time, solution pH and temperature. The Freundlich isotherm model better depicted the equilibrium data compared with the Langmuir isotherm model. Temperature was found to negatively affect the adsorption capacity of the prepared AC, which exhibited 612.1, 464.3 and 410.0 mg/g maximum MB adsorption capacities at 30, 40 and 50 C, respectively. The pseudo-second order kinetic model best described the kinetic data. HTC and NaOH activation was proven to be an effective method in preparing highly porous AC from PDS, with good potential for cationic dye removal from liquid phase.